2012
DOI: 10.1055/s-0032-1323588
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction Decreases Endochondral Ossification and Bone Strength in Female Rats

Abstract: Intrauterine growth restriction (IUGR) modifications to postnatal skeletal growth may increase adult fracture, especially in females who have greater risk of osteoporosis. Little is known about the effect of IUGR on the patterns of postnatal endochondral ossification and bone development. Here for the first time we reveal bone formation, mineralization, and strength in IUGR female rats during early postnatal life and adulthood. Endochondral ossification rate of the hypertrophic zone (HZ) and hypertrophic cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Experimental studies have also demonstrated a negative long-term effect of FGR on bone size, mineral content, and strength in weaning and adult rats, speculating that FGR decreases endochondral ossification responsiveness, and in turn, postnatal linear skeletal growth, bone mineralization, and strength (36). In our study, prenatal food restriction had a significant impact on bone mineral accrual, and rats that were born to food-restricted mothers showed lower BMC and BMD values irrespective of their birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have also demonstrated a negative long-term effect of FGR on bone size, mineral content, and strength in weaning and adult rats, speculating that FGR decreases endochondral ossification responsiveness, and in turn, postnatal linear skeletal growth, bone mineralization, and strength (36). In our study, prenatal food restriction had a significant impact on bone mineral accrual, and rats that were born to food-restricted mothers showed lower BMC and BMD values irrespective of their birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…IUGR in humans (21,28) and animals, namely pig (33,52,53), sheep (31) and rat (54), results in increased body adiposity and fibrosis (55,56). In contrast, IUGR has a negative impact on bone (34,57), cartilage (58) and skeletal muscle development (33,59) as observed in horses (18,19) and dogs (17, 60). Our results indicated an increased predisposition of IUGR-MSCs for adipogenesis and fibrogenesis which suggested that IUGR programmes the adult stem cell niche during fetal development, and this may underpin the increased accumulation of fat and fibrous tissue reported in IUGR individuals, later in life (61).…”
Section: Iugr-mscs Presented Decreased Chondrogenesis Compared To Normentioning
confidence: 99%
“…Pigs offer a relevant model to study IUGR. In pigs, IUGR occurs spontaneously, and recapitulates human IUGR features, including altered body development characterized by reduced musculoskeletal growth and a tendency to accumulate body fat post-nataly (31)(32)(33), as it is also observed in other models (16,34). Using the IUGR pig model (16,35,36), and in order to assess the effect of developmental programming on MSCs, we compared the properties of MSCs obtained from IUGR and normal newborn pig littermates.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier work found greater lean tissue mass in weanling rat pups that were given tactile stimulation during 10 min of daily maternal separation from P6 to P10 [24]. Although these results appear contradictory, it is important to remember that the neonatal stress model used in the current study exposed rat pups to a variety of stressors and for a longer duration, i.e.…”
Section: Discussionmentioning
confidence: 74%
“…In animals, stressors such as maternal separation, hypoxia, or exogenous glucocorticoid (GC) exposure in early neonatal life may permanently change stress response [15,16,18,19], body structure [20], and metabolism [21] increasing the incidence of adult chronic diseases [15,16,21,23]. In rats, MTS during early postnatal life increases weight gain [24] and decreases neuroendocrine response to stress in adult animals [25,26]. Therefore, a rat model may provide a good model to study mechanisms underlying MTS intervention to modulate neonatal stress and thereby stress-driven adipose tissue deposition and metabolism.…”
Section: Introductionmentioning
confidence: 99%